Photonic, Electronic And Atomic Collisions - Proceedings Of The Xxiv International Conference - Rivarola, Roberto D; Fainstein, Pablo D; Lima, Marco Aurelio P; Miraglia, Jorge E; Montenegro, Eduardo; Agostini, Pierre (World Scientific Publishing Company, 2006)
Contains contributions covering a range of subjects in the area of photonic, electronic and atomic collisions. This work includes the collisions of heavy particles and electrons with atoms, molecules and clusters; the coherent control of reaction dynamics using lasers and electromagnetic fields with molecules, clusters and liquids; and others.